STRATEGIIPEMBELAJARANPINKUIRIIUNTUKKMENINGKATKANN KEMAMPUANNBERPIKIRRKRITISSDAN KEMANDIRIAN BELAJARRSISWA - Darusman, Hera Haerunisa; Gusrayani, Diah; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
Thissresearch aimssto knowwtheeincreased critical thinking abilityyand independence studentt learningg by using inquiryylearninggstrategies,Â tooknowwtheddifference increase in theeabilityoof critical thinking and independence student learning from the class that uses inquiry learning strategies with the use of conventional learning. Method usediissnon-equivalentccontrolggroup design. Theppopulationiintthis study are studentoofffiveegradeelementaryyschool from Pamulihan districts. The selected sampleÂ were students of class VAAasstheeexperimental class anddstudents of classsVB asstheecontrol class at SDN Sukalilah. Instruments used is test critical thinking ability, question form independence study, observation sheet performance teacher and student activities, anecdotal records, and interview. Research results indicates that the increased in the ability of critical thinkinggand independence studenttlearningbbyuusingginquiry learning strategies. There is an increasing difference in the ability of critical thinking from the class that uses inquiry learning strategies with the use of conventional learning. There is no difference in the increase independence student learning from the class that uses inquiry learning strategies with the use of conventional learning.